Syndecans as Modulators and Potential Pharmacological Targets in Cancer Progression - Barbouri, Despoina; Afratis, Nikolaos; Gialeli, Chrisostomi; Vynios, Demitrios H.; Theocharis, Achilleas D.; Karamanos, Nikos (Frontiers in Oncology, 2014)
Extracellular matrix (ECM) components form a dynamic network of key importance for cell function and properties. Key macromolecules in this interplay are syndecans (SDCs), a family of transmembrane heparan sulfate proteoglycans (HSPGs). Specifically, heparan sulfate (HS) chains with their different sulfation pattern have the ability to interact with growth factors and their receptors in tumor microenvironment, promoting the activation of different signaling cascades that regulate tumor cell behavior. The affinity of HS chains with ligands is altered during malignant conditions because of the modification of chain sequence/sulfation pattern. Furthermore, matrix degradation enzymes derived from the tumor itself or the tumor microenvironment, like heparanase and matrix metalloproteinases, ADAM as well as ADAMTS are involved in the cleavage of SDCs ectodomain at the HS and protein core level, respectively. Such released soluble SDCs “shed SDCs” in the ECM interact in an autocrine or paracrine manner with the tumor or/and stromal cells. Shed SDCs, upon binding to several matrix effectors, such as growth factors, chemokines, and cytokines, have the ability to act as competitive inhibitors for membrane proteoglycans, and modulate the inflammatory microenvironment of cancer cells. It is notable that SDCs and their soluble counterparts may affect either the behavior of cancer cells and/or their microenvironment during cancer progression. The importance of these molecules has been highlighted since HSPGs have been proposed as prognostic markers of solid tumors and hematopoietic malignancies. Going a step further down the line, the multi-actions of SDCs in many levels make them appealing as potential pharmacological targets, either by targeting directly the tumor or indirectly the adjacent stroma.